Frecuencia de uso de la forma de tratamiento marica en Twitter (X). - Campo-Paredes, Andrés Felipe; García, Gloria Marcela Cataño (Enunciación, 2026)
Nominal forms of address (NFAs) are one of the major fields of study within variationist sociolinguistics. They are conceptualized as lexical choices that speakers use to establish social relationships within the speech act. The following article presents an analysis of the frequency and geographic distribution of the nominal form of address marica in a pan-Hispanic corpus extracted from the social media platform Twitter (now X). To this end, a big data corpus was used, comprising 122,356,443 Spanish-language tweets published between 2009 and 2016 in 188 cities across 10 different Spanish-speaking countries. Due to the overrepresentation of the NTF's use, Colombia was excluded from the analysis. The methodology employed a quantitative design that combined corpus linguistics approaches with digital sociopragmatic variation analysis. The data were processed using Python programming language libraries. The results identified a total of 8,567 occurrences of marica. Venezuela was the epicenter, followed by the United States, demonstrating usage trends that transcend geographical proximity to Colombia. The results suggest that lexical circulation in digital environments may follow patterns of network connectivity and migratory flows rather than geographical proximity, although the available data do not allow for a definitive confirmation of this. It is concluded that normalized frequency analysis is methodologically necessary for heterogeneous corpora and that digital networks can serve as laboratories for observing the diatopic variation of FTNs in real time and on a pan-Hispanic scale.